(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
Hermeneutics was first introduced for the first time since the emergence of the foundations of logic, Peri Hermeneias by Aristotle. The concept of logic and the use of rationality have become the bases for hermeneutical actions. Hermeneutics is a philosophy that explores the interpretation of meaning. The word ‘hermeneutics comes from the Greek, hermeneutics, which means interpreting, understanding, or translating. Also, hermeneutics is the name of one of the ancient Greek pantheons, namely Hermes. The ancient Greeks called him a god, while Islam calls him Prophet Idris whose job was to convey God’s messages to human beings. Next, hermeneutics is defined as the science of text interpretation. Hermeneutics is a theory about understanding the interpretation of texts which differs greatly from general understanding, leading to an aesthetic awareness of the values of criticism. What is Emilio Betti’s Hermeneutics? Hans-Georg Gadamer may be a philosopher that is closely associated with the hermeneutics of our time. He was able to link interpretive experience to education.